Gender features of etiopathogenesis, clinical and anatomical picture, tactics and results of surgical treatment of infrarenal aortic aneurysm in women - A. Ya. Bedrov; A. A. Moiseev; A. V. Baikova (Вестник хирургии имени И.И. Грекова)
The review includes the analysis of the literature data on the features of etiopathogenesis, clinic, tactics and results of treatment of infrarenal aortic aneurysm.